1994
DOI: 10.1016/s0377-1237(17)31032-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ct Scan in Partial Seizures in Children

Abstract: ABSTRAcr 50 consecutive cases of partial seizures hospitalised over a period of 2 years, were studied. cr Scans were done once at presentation and thereafter cases were followed up with repeat cr scans to evaluate treatment response wherever a treatable cause was found. cr scan diagnosis was correlated with clinical signs and other baseline investigations including an EEG. cr scan abnormality was detected in 66% cases. Single or multiple tuberculomas were noted in 24% cases, cortical atrophy in 14% cases, foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Demonstration of normal structures with ability to diagnose atrophy and demonstration of space occupying lesions, their position and nature to a certain extent, specially solid and cystic masses, tumours, abscesses, haemorrhages and infarctions. 3 Study by Kanitkar M et al showed porencephalic cyst or cerebral atrophy was seen in 21% of abnormal scans and mostly in the preschool children who gave a history of meningitis or birth asphyxia. 3 In a study conducted by Yang P et al, 17 out of 34 children with partial seizures had an abnormal CT, the commonest being atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Demonstration of normal structures with ability to diagnose atrophy and demonstration of space occupying lesions, their position and nature to a certain extent, specially solid and cystic masses, tumours, abscesses, haemorrhages and infarctions. 3 Study by Kanitkar M et al showed porencephalic cyst or cerebral atrophy was seen in 21% of abnormal scans and mostly in the preschool children who gave a history of meningitis or birth asphyxia. 3 In a study conducted by Yang P et al, 17 out of 34 children with partial seizures had an abnormal CT, the commonest being atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The yield of positive results was 46.55% which is in the range of 30-70% as quoted by various authors. [3,17,18,19] Maytal J et al (2000) showed that fifty-two patients (78.8%) had normal CT results and 14 patients (21.2%) had abnormal CT results. Seizure cause was considered cryptogenic in 33 patients, of whom 2 (6%) had abnormal CT results; neither patient required intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A study done by Kanitkar M et al concluded that CT scan abnormality was detected in 66% cases. 19 Single or multiple tuberculomas were noted in 24% cases, cortical atrophy in 14% cases, focal calcification in 10%, haemorrhage in 3% and subdural effusions in 2%.…”
Section: Malementioning
confidence: 93%
“…One of them was metachromatic the importance of imaging in the seizure in children. A study done by Kanitkar M et al concluded that CT scan abnormality was detected in 66% of cases [10]…”
mentioning
confidence: 98%